Evaluation of Lecturer Teaching Performance Using AHP and SAW Methods - Benny Daniawan (bit-Tech, 2018)
The lecturer performance evaluation activity is the routine of an university in continuously improving internal quality as an evaluation and development of educational institutions. Buddhi Dharma University Tangerang, every semester evaluates lecturers' performance. But the results obtained are not optimal, this is due to the absence of an effective and efficient method in determining the results, especially in the Faculty of Science and Technology, Information System Departement. The assessment process is carried out by distributing questionnaire papers and filled out by students. This study aims to analyze the results of the questionnaire, calculated by combining the Analytical Hierarchy Process (AHP) method for weighting and combined the Simple Addictive Weighting (SAW) method for ranking. The results obtained were the level of criteria weighting accuracy reached 90.39% with 28 lecturers which teaching 47 subjects in the Information Systems Departement.